Modern medical toxicology - Pillay, V. V. (Jaypee Brothers Medical Publishers (P) Ltd, 2013)
The first ever Indian textbook exclusively devoted to medical toxicology with an outstanding track record of more than 15 years of uninterrupted print editions and reprints. The latest (4th) edition has been completely revamped with brand new, current information presented in a totally different format. Incorporation of more than 200 colour images and several hundred tables, boxes and bulleted lists. Every commonly encountered xenobiotic (poison/toxin/drug/chemical) has been dealt with in a comprehensive manner with regard to source, physical appearance, toxicokinetics, fatal dose, signs and s.